Pengaruh Metode Bercerita Berbantuan Media Gambar Terhadap Keterampilan Berbicara Siswa Kelas III SDN 1 Sakra Selatan - Azhari, Ahmad; Darmiany, Darmiany; Husniati, Husniati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2021)
This study aims to determine the effect of picture-assisted storytelling method on the speaking skills of third grade students of SDN 1 Sakra Selatan. This type of research is experimental research, with a Quasi-Experimental Design type of Nonequivalent Control Group Design. The population in this study were all third-grade students of SDN 1 Sakra Selatan. Sampling was carried out using the Census/ Total Sampling technique. Data collection methods in this study used observation sheets and performance test. Observation sheets are used to determine the implementation of learning with the storytelling method assisted by picture media, while performance tests are used to assess student’s speaking skills. Based on the results of the Independent Sample T-Test, the significance value or Sig (2-tailed) is 0,002, which means it is less than 0,05. This shows that Ho is rejected and Ha is accepted, so it can be concluded that there is an influence of the picture-assisted storytelling method on the speaking skills of the third-grade students of SDN 1 Sakra Selatan.